AMBIGUITAS PENGUJIAN TERHADAP PERATURAN DAERAH - Bambang Giyanto (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Law No 32 Year 2004 about Local Government offers local government wide authority to manage and regulate their citizens’ interests and aspiration. Correspondingly, local government with local representatives formulates local regulations (Perda). In terms of the type and level as pointed out in the Law No 10 Year 2004 regarding Regulation Formulation, Perda represents the lowest level law. Therefore, Perda holds more afflictions than any other laws in the sense that it has to be in accordance with the higher level laws. This condition often causes unexpected snags in the local autonomy implementation. Up to a certain degree, disharmony with the higher level laws is unavoidable due to conflicts of interest. With regard to local regulation annulations, Law No 32 Year 2004 Article 145 verse 3 states that local regulation annulation is regulated by Presidential Regulation (Perpres). In practice, local regulations are annulled by Internal Affair Ministerial Regulation (Permendagri). Substantial inconsistency between Perda and the central government regulation as well as the regulation examination incongruous with the Law No 32 Year 2004 Article 145 verse 3 instigates ambiguity which should be eliminated in order that local autonomy performs properly.